Elucidating Ionization Behavior: Potentiometric Titration for Precise Determination of pKa Values in Medicinal Chemistry - Safiye Nihal Aydoğdu; Durişehvar Ünal (Pharmata)
The determination of pKa values holds paramount importance in the field of medicinal chemistry, serving as a critical parameter for understanding the ionization behavior of pharmaceutical compounds. This study employs potentiometric titration as a precise method to elucidate the pKa values of diverse molecules. The experimental methodology involved a carefully controlled titration setup, utilizing a pH meter to monitor the titration curve and identify inflection points corresponding to the dissociation of acidic or basic functional groups.